Pengaruh Pemberian Ikan Kutuk terhadap Perubahan Status Gizi pada Bayi Gizi Kurang Usia 6–24 Bulan di Klinik Pratama Rawat Inap Al Bashiroh Turen - Anna Tyas Maharani; Rani Safitri (Institut Nalanda, 2026)
Malnutrition in infants aged 6–24 months remains a significant public health issue in Indonesia. This condition can impact growth, motor development, and immune system development. One local food-based intervention being developed is the provision of catfish (Channa striata) due to its high protein, albumin, and essential amino acid content, which play a role in improving nutritional status (Ministry of Health, 2022). This study aimed to determine the effect of catfish administration on changes in nutritional status in malnourished infants aged 6–24 months. This study used a quantitative design with a comparative approach between the control and intervention groups. A sample of 30 infants was selected using total sampling. Data were analyzed using cross-tabulation to assess changes in nutritional status before and after the intervention. The results showed a significant improvement in nutritional status in the intervention group, with all infants (100%) in the good (high) nutritional category after being administered catfish. However, no significant changes were observed in the control group. The provision of catfish did improve the nutritional status of infants aged 6–24 months who were classified as malnourished.